Character Education through Tapak Suci: A Qualitative Case Study in Indonesian Senior High School - Eka Hidayati; Deny Hadi Siswanto; Endang Susetyawati; Kintoko Kintoko (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2026)
Character education is an increasingly prominent aim of contemporary schooling, yet the processes by which culturally and religiously grounded extracurricular programs shape student character remain under-examined in non-Western contexts. This qualitative case study examines how participation in Tapak Suci, a Muhammadiyah martial arts extracurricular activity, contributes to character formation at a private senior high school in Yogyakarta. Information was collected from 12 students, 4 coaches, and 2 school administrators via 18 semi-structured interviews, 40 hours of participant observation, and document analysis conducted between March and May 2025. Analysis followed Miles and Huberman’s interactive model with systematic thematic coding and triangulation across sources. Findings indicate that Tapak Suci supports the development of religious commitment, discipline, punctuality, responsibility, mutual respect, and self-control. These outcomes were sustained through regular training routines, explicit moral instruction, coach role-modelling, and organizational rituals that integrate practice with moral discourse. The study clarifies mechanisms by which extracurricular practice translates into enduring character dispositions and discusses limits to transferability given the single-site design. Implications include the value of aligning extracurricular structure with explicit character objectives and of training coaches as intentional character educators. This research contributes empirical evidence from an understudied cultural context and offers actionable recommendations for educators seeking to harness extracurriculars for character education.